Personal finance - Kapoor, Jagdish R. , 1937-; Dlabay, Les R.; Hughes, Robert James , 1946 (The McGraw-Hill/Irwin series in finance, insurance, and real estate, 2012)
Provides many financial planning tools using a step-by-step approach to help students identify and evaluate choices as well as understand the consequences of decisions in terms of opportunity costs